A5.13 Antibody responses to common viruses in patients with rheumatoid arthritis. (13th February 2015) - Sherina, N; Sigridur, H; Bengtsson, C; Alfredsson, L; Klareskog, L; Lundberg, K
Abstract : Background and objectives: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune condition where HLA DRB1 shared epitope (SE) alleles and cigarette smoking constitute well-established risk factors. Still, current knowledge does not explain the whole risk for developing RA. An attractive hypothesis has been that RA is triggered by an infection, and since the early eighties, when the Epstein Barr virus (EBV) was first linked to RA, a number of studies have investigated the role of viruses in RA aetiology, although with conflicting results. Since most studies have been small, or poorly controlled, or not set in the context of anti-citrullinated protein antibodies (ACPA), SE and smoking, it has been difficult to draw any conclusions. Hence, to further elucidate the role of common viruses in RA aetiology, we have analysed the prevalence of anti-virus antibodies in the well-characterised population-based RA case-control cohort EIRA. Material and methods: The antibody response to EBV, cytomegalovirus (CMV) and parvovirus B19 was analysed by ELISA in serum from 1000 EIRA RA cases and 700 EIRA controls. Data on ACPA, smoking and SE status was obtained from the EIRA database. Fisher's exact test and Mann-Whitney U test for independent groups were used in the statistical analyses of antibody levels. Unconditional logistic regression analysis was used to calculate odds ratios (OR) with 95% confidence intervals (CI) for the association of anti-virus antibodies with different RA subsets. The additive interaction was evaluated between smoking/SE and virus exposure in ACPA+ RA. Results: There was a high prevalence of anti-virus antibodies in EIRA, but with no significant differences between RA cases and controls (98.3% vs. 97% for anti-EBV IgG; 75.8% vs. 72.8% for anti-B19 IgG; 72.2% vs. 75.9% for anti-CMV IgG, in RA cases and controls, respectively), and ACPA had no effect on presence/absence of anti-virus antibodies. When comparing anti-virus antibody levels, anti-EBV IgG and anti-B19 IgG levels were significantly lower in ACPA+ RA compared to controls, and there was an interaction between low levels/absence of both anti-EBV and anti-B19 antibodies and SE in the development of ACPA+ RA, while smoking had no effect. Conclusion: High levels of virus antibodies were not positively associated with RA, irrespective of ACPA, SE or smoking status. If anything there was an inverse association. Hence, our study cannot support a role for these specific viruses in RA aetiology.